Toleransi dalam Tafsir al-Qurṭubī: Analisis Relasi Antaragama bagi Moderasi Beragama di Sekolah - Retno purwaningsih (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The increasing phenomenon of intolerance and radicalism in Indonesian educational environments demonstrates the urgent need for strengthening religious moderation based on strong theological foundations. This study examines the concept of tolerance in the tafsir Al-Jāmi' li Aḥkām al-Qur'ān by Imam al-Qurṭubī and its relevance to strengthening religious moderation in schools. Tolerance is a fundamental value in plural societies, particularly in the context of Indonesia's diverse education system. The phenomenon of intolerance and radicalism infiltrating the educational sphere demands a strengthened understanding of tolerance based on authoritative Islamic sources. Using library research methodology with a qualitative-descriptive approach, this study analyzes al-Qurṭubī's interpretation of tolerance verses in the Qur'an, specifically QS. al-Baqarah [2]: 256, QS. al-Kāfirūn [109]: 6, QS. al-Mumtaḥanah [60]: 8-9, and QS. al-Ḥujurāt [49]: 13. The findings reveal that al-Qurṭubī constructs the concept of tolerance based on five main principles: prohibition of coercion in religion (lā ikrāh), recognition of plurality (i'tirāf bi al-ta'addudiyyah), universal justice (al-'adl al-'āmm), peace and goodness (al-silm wa al-iḥsān), and dialogue with wisdom (al-ḥiwār wa al-ḥikmah). This concept is highly relevant for strengthening religious moderation in schools through curriculum integration, habituation of mutual respect, teacher role modeling, and creation of an inclusive school environment. This research provides theoretical and practical contributions to the development of character education based on religious moderation in Indonesia, while offering an alternative educational approach rooted in classical Islamic intellectual heritage.